Estambul: iconografía de una fascinación - Almarcegui Elduayen, Patricia (Revista de Filología Románica, 2011)
This article presents a series of iconographic representations that show how Istanbul has fascinated both Orient and Occident. The elements that attracted attention of the travellers have been painted in the works of several artists, in whose pictures we can find sultan’s portraits, odalisques, harems and lanscapes, like views of the Golden Horn or the Hagia Sophia.